2022
DOI: 10.2478/hukin-2022-0066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leg Stiffness Regulated by Different Landing Styles on Vertical Drop Jump Performance

Abstract: The purpose of this study was to investigate the effects of stiffness regulated by landing styles on drop jump performance. Twenty-four male lacrosse athletes performed drop jumps with stiff (ST), self-selected (SS), and soft (SF) landing from a 0.42 m box. Leg stiffness, ground contact time, depth, jump height, maximum ground reaction force (GRF), GRF at the start of the propulsive phase, mean power, peak power, and the reactive strength index (RSI) were calculated. The results showed that jump height and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…These results are in line with a recent investigation by Ando, et al (2021) [ 21 ], which showed that medial gastrocnemius stiffness (measured during a 15 cm drop jump as the shear modulus through ultrasound shear wave elastography) correlated with the same performance parameters (RSI and JH) but not with the contact time. In addition, our results are in line with other studies [ 38 , 39 ] in which the authors demonstrated that drop jumps performed with different modes and instructions show different responses. In particular, the authors showed that when participants were asked to reach the maximum jump height or to make their best effort, without further instruction, they obtained the best JH, with no correlation with contact time.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with a recent investigation by Ando, et al (2021) [ 21 ], which showed that medial gastrocnemius stiffness (measured during a 15 cm drop jump as the shear modulus through ultrasound shear wave elastography) correlated with the same performance parameters (RSI and JH) but not with the contact time. In addition, our results are in line with other studies [ 38 , 39 ] in which the authors demonstrated that drop jumps performed with different modes and instructions show different responses. In particular, the authors showed that when participants were asked to reach the maximum jump height or to make their best effort, without further instruction, they obtained the best JH, with no correlation with contact time.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the peak vertical reaction force during SDVJ was smaller than that during SDL despite the same landing height between the two landings 13 . Additionally, the vertical ground reaction force during the landing phase is not correlated with jumping height in the drop vertical jump task 50 . The peak vertical ground reaction force is usually observed within 63.5 ms after initial contact during single-leg landing 34 and is not associated with subsequent jumping after landing.…”
Section: Discussionmentioning
confidence: 82%
“…Stiffness, although its optimal regulation enhances performance and power output [59][60][61], was not found to be a determining feature for VDJ performance [7,62]. Nevertheless, K VERT was significantly higher in the VDJ than in the HPRJ.…”
Section: Discussionmentioning
confidence: 99%